HUBUNGAN ANTARA DUKUNGAN SOSIAL TEMAN SEBAYA DENGAN PENYESUAIAN DIRI PADA MAHASISWA RANTAU PAPUA DI UNIVERSITAS MUHAMMADIYAH GORONTALO - Fendi Ntobuo; Nur Qomariah Nteya (program studi psikologi, 2023)
This study aims to determine the relationship between peer social support and adjustment in Papuan overseas students at Universitas Muhammadiyah Gorontalo. Data collection was carried out using a questionnaire in the form of a peer social support scale and a self-adjustment scale. The sampling technique in this study used total sampling with a total sample of 23 respondents. Data analysis uses a product-moment correlation of 0.040 with a p-value <0.05, meaning that there is a positive and significant relationship between peer social support and adjustment to Papuan students, this shows that the higher the peer social support, the higher the adjustment and vice versa.